The Infulence of Various Food Intake on Body Fat Distribution among Young Healthy Population - Dwi Prijatmoko; Sulistiyani Sulistiyani; Dyah Setyorini; Hestieyonini Hadnyanawati; Elyda Akhya Afida Misrohmasari; Anisa Nur Syabila (Health Notions, 2022)
Food intake is the amount of food obtained by the body via daily food consumption that consists of energy, carbs, fat, and protein. The distribution of fat will be affected by an imbalance in food consumption. The distribution of body fat is classified as either android or gynoid obesity. Someone who has abdominal obesity is more likely to develop metabolic syndrome. This study aims to determine the influence of food intake on fat distribution in dental student of Faculty of Dentistry, University of Jember. Analytic observational research methods were applied in this study. The population comprised of 109 students from the Faculty of Dentistry at the University of Jember. The research procedures comprised instructing, measuring height, weight, the waist-hip circumference ratio, completing the food intake measurement sheet based on 24 hours food recall, data conversion, and data entry. The influence of food intake on fat distribution was determined using logistic regression data analysis. The results revealed that food intake had an effect on fat distribution. The male group's effect was energy, while the female group's influence was carbohydrates and fat, according to the study's findings. Food consumption has a substantial impact on the distribution of body fat among dental students at the Faculty of Dentistry Keywords: food intake; fat distribution; abdominal obesity; waist-hip ratio